PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI INTERPERSONAL TERHADAP KOMITMEN AFEKTIF DOSEN STKIP MUHAMMADIYAH BONE - Sudirman Sudirman (Universitas Negeri Jakarta, 2018)
The objective of this research is to obtain information about the effect of transformational leadership and interpersonal communication on lecturer affective commitment. It was quantitative research with survey method in STKIP Muhammadiyah Bone. The research was conducted to all lecturer of STKIP Muhammadiyah Bone by using a survey method with path analysis applied in testing hypothesis.The number 60 employees as sample was selected by using Slovin formula.The research conlude: (1) There is a direct positive effect of transformational leadership on affective commitment . (2) There is a direct positive effect of interpersonal communication on affective commitment. (3) There is a direct positive of transformational leadership on interpersonal communication.